The validity of cycling power recorded by the elite axiom ergometer - Nesi, X.; Bosquet, L.; Carter, H.; Dekerle, J.; Pelayo, P. (Journal of Human Movement Studies, 2006)
The purpose of the present study was to test the validity of average power output measurement by a new stationary ergometer, the Elite Axiom, against the SRM Powermeter. An experienced cyclist completed, firstly, a series of 3min square wave exercises at different powers output at 90rpm, and secondly, a series of 3min square wave exercises at an identical target power output with different imposed cadences. For all the tests, the cyclist's bicycle, fitted with a SRM Powermeter, was attached to the Elite Axiom ergometer. Results indicated that average power output measured by the Elite Axiom ergometer was significantly higher compared with the SRM Powermeter (20.3%). However, the average power output values measured by both SRM and Elite Axiom were strongly related (r2=0.975; p<0.01). A corrective equation makes it possible to adjust the overestimation in average power output by Elite Axiom ergometer (average power output=83.1% of average power output by Elite Axiom). These characteristics make the Elite Axiom a useful measurement System of the cycling average power.